Gender, culture and STEM: Counter-intuitive patterns in Arab society - Naomi Friedman-Sokuler; Moshe Justman (Bar-Ilan University, Department of Economics, 2019)
Arab society in Israel offers a counter-example, which calls into question the hypothesis that the male advantage in STEM decreases as gender equality in society increases. Analyzing administrative longitudinal data on students in Hebrew- and Arabic-language schools in Israel, all operating within the same centralized education system, we find that the gender achievement-gap favoring girls in Arabic schools, the ethnic group characterized by less gender equality, is greater than the gender gap favoring girls in Hebrew schools. Moreover, male dominated STEM matriculation electives in Hebrew schools are female-dominated in Arabic schools, controlling for prior achievement in mathematics. We show that these patterns are not dependent on socioeconomic or school characteristics but rather reflect ethnic differences in the gendered effect of prior achievement on subject choice. While in Hebrew-language schools the gender gaps favoring men in physics, computer science and advanced mathematics electives increase in early mathematical achievement, in Arabic-language schools gender gaps favoring men are non-existent and even reversed among top achieving students.
Keywords: I21; J15; J16; J24; 330; culture; gender gap in mathematics; STEM; Arab society; educational choice